2009
DOI: 10.1088/0960-1317/19/6/065012
|View full text |Cite
|
Sign up to set email alerts
|

The electrical conduction and dielectric strength of SU-8

Abstract: This paper presents a study on the dielectric behavior of SU-8 photoresist. We present measurements on the leakage current levels through SU-8 layers of varying thickness. The leakage current is dominated by thermionic emission. We have further determined the dielectric strength of SU-8 to be 4.4 MV cm −1 . The remarkably high dielectric strength allows the material to be used for high-voltage applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 16 publications
0
46
0
Order By: Relevance
“…Typical values for SU8 dielectric strengths are 100-150 V/lm and thickness dependent. Hence, for a 90 nm thick SU8 layer, the breakdown voltage is very close to 13 V. 18 The reverse sweep showed a distinct change in the flatband voltage shifting to about 1.3 V for 615 V sweeping voltage range. The hysteresis is attributed to the presence of SWCNTs as a floating gate and results from the charging and discharging of the SWCNTs when negative and positive voltages are consecutively applied.…”
Section: -2mentioning
confidence: 84%
“…Typical values for SU8 dielectric strengths are 100-150 V/lm and thickness dependent. Hence, for a 90 nm thick SU8 layer, the breakdown voltage is very close to 13 V. 18 The reverse sweep showed a distinct change in the flatband voltage shifting to about 1.3 V for 615 V sweeping voltage range. The hysteresis is attributed to the presence of SWCNTs as a floating gate and results from the charging and discharging of the SWCNTs when negative and positive voltages are consecutively applied.…”
Section: -2mentioning
confidence: 84%
“…In addition, the dielectric strength of SU-8 is 4.43 ± 0.16 MV cm −1 which is remarkably high for a polymer material. It is reported that for 15 μm thick SU-8 has voltage breakdown of around 7 kV and increases over the thickness (Melai et al 2009). The simulated pullin voltage V p from the centre conductor is 10.5 V and the calculated maximum RF power is 2.2 W. There are 32 capacitance steps which change linearly from 102.23 fF to 3.57 pF with an incremental capacitance step of 0.11 pF as demonstrated in Fig.…”
Section: Electro-magnetic Simulationsmentioning
confidence: 99%
“…It exhibits many properties that make it suitable for the microfabrication of particle detectors, such as the ability to be structured in a broad range of thicknesses and with high aspect ratios [2], excellent smoothness [3] and transparency [4] (desirable characteristics for the optical materials used in detectors such as scintillators), a relatively high dielectric strength [5] (desirable in devices making use of high electric fields, such as gaseous ionization detectors), and finally low outgassing [6] (necessary to avoid the pollution of the high vacuum environments in which many detectors work) and radiation tolerance [7]. Here we review several particle detector technologies making use of microstructures obtained by SU-8 processing.…”
mentioning
confidence: 99%